The Effect of Health Education on Pregnant Women’s Knowledge About Perineal Massage in Allang Village, West Leihitu District - Umamity, Syahfitrah; Windari, Arindiah P (UNIMUS Web Conferences, 2026)
Background: Perineal rupture is a common complication of vaginal delivery, especially among primigravida mothers, and can lead to maternal morbidity and discomfort. Limited knowledge among pregnant women regarding preventive measures, such as perineal massage, contributes to the high risk of perineal trauma during childbirth. Therefore, effective health education is needed to improve pregnant women’s understanding of perineal massage as a non-pharmacological intervention to increase perineal elasticity. Objective: To emphasize the target of the research This study aimed to analyze the effect of health education on pregnant women’s knowledge regarding perineal massage. Method: This study employed a quasi-experimental design with a one-group pretest–posttest approach involving eight pregnant women in Allang Village selected using total sampling. Data were collected using a 20-item knowledge checklist administered before and after the health education intervention. Data normality was tested using the Shapiro–Wilk test, and differences in knowledge scores were analyzed using the Paired Sample t-Test. Ethical principles, including informed consent and confidentiality, were applied throughout the study. Results: The results showed a significant increase in pregnant women’s knowledge after the health education intervention, with mean knowledge scores rising from 6.88 to 17.00 (p = 0.000). Discussion: The increase in knowledge can be explained by learning theory, which suggests that structured health education improves understanding and retention of information. Health education enhances cognitive processes by providing clear information, demonstrations, and opportunities for discussion, thereby increasing awareness of perineal massage as a preventive strategy for perineal rupture. Conclusion: Health education significantly improves pregnant women’s knowledge about perineal massage and can be applied as an effective educational strategy in antenatal care to support the prevention of perineal rupture during childbirth.